Disability, human rights, and contract law / Eliza Varney, University of Nottingham. - Varney, Eliza, 1978- (Law in context., 2025)
An initial glance at the intricate web of the English legal system may perceive human rights and private law as paths leading to different realms. In this vision, contract law, shaped by economic concerns, is confined to a role of enforcing agreements. Yet, given ageing population trends and the increase in the number of people with mental health conditions, such as dementia, entering into grossly asymmetrical contracts, we must re-assess the lens through which we perceive contract law. This book calls for a re-examination of the role of contract law in light of the UN Convention on the Rights of Persons with Disabilities (UNCRPD), insisting on an approach that responds to both economic and social concerns. The book aims to contribute towards bridging the areas of disability equality and contract law, questioning the compatibility of key principles and doctrines in contract law with UNCRPD values, including autonomy and human dignity.